Spiritual serenade and a night of Muslim spirituality - Yussof, Sheila Ainon (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2013)
Thanks to the initiative of IAIS Malaysia, Fajr Symphony, Crescent Collective and Urban Village, ‘Desert Rose’ from Africa made its debut performance in the IAIS Conference Hall on 21st June 2013, where a common feeling pervaded that “music connects people” and “music unites people, in a world of differences”. By late evening the Hall was packed with people from various communities and creeds wanting to be healed from the wounds of divisiveness and cultural insensitivities, or just waiting to be serenaded and inspired by spiritual songs after a day of frayed nerves and work tension.